2018
DOI: 10.3390/nu10111619
|View full text |Cite
|
Sign up to set email alerts
|

Role of Selenoprotein F in Protein Folding and Secretion: Potential Involvement in Human Disease

Abstract: Selenoproteins form a group of proteins of which its members contain at least one selenocysteine, and most of them serve oxidoreductase functions. Selenoprotein F (SELENOF), one of the 25 currently identified selenoproteins, is located in the endoplasmic reticulum (ER) organelle and is abundantly expressed in many tissues. It is regulated according to its selenium status, as well as by cell stress conditions. SELENOF may be functionally linked to protein folding and the secretion process in the ER. Several stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…However, several other lines of evidence suggest that SELENOF may act as an Se-dependent oncogenic protein. SELENOF can be regulated by both Se status (as indicated also in our study) and endoplasmic reticulum (ER) stress, and several SELENOF genetic variants have been associated with an altered risk at the different cancer sites, including CRC [ 8 , 29 ]. Notably, previous cell and mouse-model studies suggest that higher levels of SELENOF may potentially contribute to favorable growth conditions for the cancerous cells in the colorectum, by reducing cellular ER stress and nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) activation [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 71%
“…However, several other lines of evidence suggest that SELENOF may act as an Se-dependent oncogenic protein. SELENOF can be regulated by both Se status (as indicated also in our study) and endoplasmic reticulum (ER) stress, and several SELENOF genetic variants have been associated with an altered risk at the different cancer sites, including CRC [ 8 , 29 ]. Notably, previous cell and mouse-model studies suggest that higher levels of SELENOF may potentially contribute to favorable growth conditions for the cancerous cells in the colorectum, by reducing cellular ER stress and nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) activation [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 71%
“…There are some selenoproteins, localized to the endoplasmic reticulum, which perform regulatory function in protein folding. This group include following selenoproteins: SelF, SelM, SelN, SelK, SelT, SelS and ID2 [11,43]. For example, SelF ensures quality of disulfide bonds formation during folding process due to interplay with UDP-glucose:glycoprotein glucosyltransferase [11].…”
Section: Selenium Status and Its Biological Importance: Selenium In Tmentioning
confidence: 99%
“…In addition to Gpxs 1, 3 and 4, our results also revealed a relatively lower expression of Selenof in response to a low-Se diet, whereas its expression was significantly higher in both Se-adequate and Se-supplemented groups. As a "thioredoxin-like" selenoprotein, SELENOF is believed to perform oxidoreductase roles and is differentially expressed under adaptive and acute cellular stress conditions and changes to the Se levels [101][102][103]. It has been shown that, as an ER-resident selenoprotein, SELENOF is implicated in unfolded protein response (UPR), protecting the accumulation of unfolded or misfolded proteins in ER and thereby mitigating ER stress in cells [101].…”
Section: Expression Of Gpx1 Gpx3 Gpx4 Selenof Bcl-2 and P21mentioning
confidence: 99%
“…In any case, these findings reasonably highlight that expression of Selenof is regulated in a tissue-specific manner and responds differentially to Se levels. Our understanding of the regulation of this selenoprotein, both at transcriptional and translational levels, in different stress-related and pathologic conditions [102,103] is insufficient and further focused studies will help understand its physiological function in detail.…”
Section: Expression Of Gpx1 Gpx3 Gpx4 Selenof Bcl-2 and P21mentioning
confidence: 99%